Isostatic systems and tectonic mechanisms present in Argentina - Introcaso, Antonio (1997)
It is well known the diversity of geological structures present in Argentina. This makes it possible to analyze the vertical mobility throughout five selected cases in which different isostatic systems act. They are: Airy (+), (-) for an Andean section compensated on 33° S; Airy (-), (+) for the decompensated Salado basin; regional (or Vening-Meinesz's) to explain - although partially - the imperfect compensation ofthe Córdoba ranges; Airy and Pratt (thermal) systems combined to explain the Andean section compensated on 25° S; and Rudzki (+), (-) to explain - in part - the decompensation ofthe 50°20' S Austral basin section. At the same time, we have considered the following mechanisms: shortening (on the Andes and Córdoba Ranges); thermal expansion (that we add to the Andean section on 25° S); stretching, thermal deactivation and load subsidence and load subsidence on the Salado and Austral basins. By analyzing not only the compensation level but also either the most adequate isostatic system or the involved mechanisms, a better understanding ofthe origin and evolution of each structure can be achieved.